Acteoside and related phenylethanoid glycosides in Byblis liniflora Salisb. plants propagated in vitro and its systematic significance - Jan Schlauer (Acta Societatis Botanicorum Poloniae, 2011)
From plantlets of Byblis liniflora Salisb. (Byblidaceae), propagated by in vitro culture, four phenylethanoid glycosides - acteoside, isoacteoside, desrhamnosylacteoside and desrhamnosylisoacteoside were isolated. The presence of acteoside substantially supports a placement of the family Byblidaceae in order Scrophulariales and subclass Asteridae. Moreover, the genera containing acteoside are listed; almost all of them appear to belong to the order Scrophulariales.